answersLogoWhite

0

  • Math and Arithmetic

What does one sixth plus two thirds equal?

User Avatar

Wiki User

βˆ™ 2013-05-08 17:21:08

Best Answer
Copy

5/6

2013-05-08 17:21:08
This answer is:
πŸ€“
🀯
πŸ€”
User Avatar

Your Answer

Loading...

Related Questions

What plus what equals two-thirds?

1 third plus one third =============== There are many other fraction combinations which equal two-thirds. One, for example, is one-half plus one-sixth.


What is one sixth plus one sixth plus one third?

four-sixth or two-thirds


What does one half plus two thirds equal?

seven sixths so 1whole and a sixth


What is one sixth plus two thirds?

it equals five sixth.


What is one-sixth plus two-thirds?

5 sixths


Are two thirds and one sixth equal?

no , two thirds is the same as four sixths


What is three sixth plus one sixth?

it's 2/3 (two thirds)


What is four and two thirds plus five and one sixth?

Nine and five sixth


Is four sixth equal to one third?

No, two-thirds


One and half plus two and two thirds?

Four and one sixth.


One third plus two sixth equals?

That would be two thirds.


DOES One third plus two thirds equal one?

I believe that it does equal one!


What is one sixth plus one third plus one half equal?

ONE


What is negative one sixth plus negative two thirds?

The sum is -5/6


Two and two thirds plus two and two thirds equal?

five and one third


What does one fourth plus one sixth equal?

1/4 + 1/6 = 3/12 + 2/12 = 5/12


What is 5 and 2 thirds plus 4 and one half?

it equals 10 and 1 sixth


What is the LCD of one sixth and two thirds?

A sixth.


What five eights plus two thirds minus one fourth?

Five eights plus two thirds minus one fourth is equal to 1.04


What is one third plus one ninth plus one sixth equal?

11 over 18


What does One ninth plus two thirds equal?

7/9


What is two thirds plus one seventh equal?

17/21


What does one third plus two sixths equal?

Two thirds


What does two thirds plus one twelfths equal?

3/4


Two thirds plus one sixth plus one sixth is?

(2/3) + (1/6) + (1/6) = (4/6) + (1/6) + (1/6) = (6/6) = 1